PENGARUH PROMOSI JABATAN, LINGKUNGAN KERJA DAN PENGAWASAN TERHADAP KINERJA PEGAWAI MELALUI MOTIVASI KERJA - Margiyanti; Titing Widyastuti (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The current condition of employee performance at the DKI Jakarta Provincial Tourism and Creative Economy Office is felt to be not optimal. The problems encountered by the author during direct observation during the author's work at the Old Town Area Management Unit, DKI Jakarta Provincial Tourism and Creative Economy Office, were encountered by several employees who in the morning were enthusiastic about working and after entering the afternoon some employees began to relax at work, sometimes even some employees were just busy playing social media. The research was carried out at the Old Town Area Management Unit of the DKI Jakarta Provincial Tourism and Creative Economy Office with a research population of 183 employees, sampled based on the slovin formula so that a sample of 126 respondents was obtained, for data collection using questionnaire method techniques, and direct observation. And for data analysis using the Smart Partial Least Square (PLS) analysis method version 3.0, for data tests used in this study are reliability tests, validity tests, statistical tests and classical assumption tests. There is a positive and significant influence of Promotion on performance. There is a positive and significant influence of promotion on employee motivation. There is a positive and significant influence of the work environment on employee performance.There is a positive and significant influence of the work environment on work motivation. There is no effect of Supervision on performance. There is no effect of supervision on work motivation. There is a positive and significant influence of work motivation on employee performance. Work motivation is able to mediate Promotion to Employee Performance positively and significantly. Work motivation has not been able to mediate the work environment on employee performance positively Work motivation has not been able to mediate supervision of employee performance.